Production of Collagens and Protein Hydrolysates with Antimicrobial and Antioxidant Activity from Sheep Slaughter By-Products - Alessandra Roseline Vidal; Rogério Luis Cansian; Renius de Oliveira Mello; Ivo Mottin Demiate; Aniela Pinto Kempka; Rosa Cristina Prestes Dornelles; José Manuel Lorenzo Rodriguez; Paulo Cezar Bastianello Campagnol (MDPI AG, 2022)
This work aimed to produce collagens and hydrolysates with antimicrobial and antioxidant activity from sheep slaughter by-products. The by-products (sheep and lamb) were treated and extracted. The collagens were hydrolyzed with the enzyme Alcalase®. The spectra of collagens and hydrolysates were similar (amide bands I, II, III, A, B). The bands presented by the collagens (α1, α2, β) were characteristic of type I collagen. The hydrolysates showed molecular weight peptides equal to/lower than 15 kDa. Collagens had a denaturation temperature of 39.32 (lamb) and 36.38 °C (sheep), whereas the hydrolysates did not undergo thermal transition. Hydrolysates showed lower values of antioxidant activity (AA) than the collagens. The collagens from lamb and from sheep displayed an AA of 13.4% (concentration of 0.0002%) and 13.1% (concentration of 0.0005%), respectively. At the concentration of 0.0020%, the lamb hydrolysates displayed an AA of 10.2%, whereas the sheep hydrolysates had an AA of only 1.98%. Collagen also showed higher antimicrobial activity compared to hydrolysates, requiring a lower concentration to inhibit the microorganisms tested. Sheep slaughter by-products proved to be a viable source for obtaining protein hydrolysates and collagens with antimicrobial and antioxidant activity, which can be applied in the development of nutraceuticals beneficial to human health.